Upaya Peningkatan Keterampilan Bahasa Anak Usia 5-6 Tahun melalui Media Alphabet Boxes - Alam Tarlam; Neng Awalia Farida; Balqis Raudhatul Khodijah (Jurnal El-Audi, 2024)
This study aims to determine the development of children's language skills through the Alphabet Boxes media carried out in group B RA Persatuan Islam 80 Kota Sukabumi. This study uses a collaborative classroom action research type with the Kemmis & Mc Taggart model. The stages of the research carried out consist of planning, implementation, observation, and reflection. The subjects of the study were 23 children in group B RA Persatuan Islam 80 Kota Sukabumi, and the object of the research was the improvement of children's language skills through the use of Alphabet Boxes media. Data collection techniques used observation, interviews, and documentation. The instruments used in the observation used research sheets, then documentation was carried out using a cellphone camera in the form of photos and videos of all children's activities during the activity and interviews using interview guidelines with group B teachers to determine the conditions and problems faced. The media used by researchers were Alphabet Boxes, this is a pre-existing media and is commonly used by Montessori practitioners, namely loose letters (movable alphabet), Flashcard letters and pictures. However, the format has been slightly modified to allow children to play individually and outside of teacher-directed learning, as researchers believe that playing while learning is the most effective learning method for children.